Manifesta 3 : European Biennial of Contemporary Art 2000. - Bonami, Francesco; Bouman, Ole; Cufer, Eda; Grzinic, Marina; Hlavajova, Maria; Mastnak, Tomaz; Peljhan, Marko; Potrc, Marjetica; Rhomberg, Kathrin; Zabel, Igor; Manifesta 3, European Biennial of Contemporary Art, Ljubljana, 2000 (Ljubljana : Ministry of Culture of the Republic of Slovenia, 2000)
A 12 ; Abdessemed, Adel ; Althamer, Pawel ; Bajevic, Maja ; Berti, Simone ; Biemann, Ursula ; Boden, Roland ; Bule, Agnese ; Calovski, Yane ; Frangouli, Nayia ; Collins, Phil ; Conijn, Joost ; Dabernig, Josef ; Darke, Colin ; Elmgreen, Michael ; Dragset, Ingar ; Fathwinter ; Fischer, Urs ; Geiger, Marcus ; Goren, Amit ; Ivanov, Pravdoliub ; Jelavic, Ivana ; Jewesbury, Daniel ; Kiaer, Ian ; Kameric, Sejla ; Koo Jeong-a ; Krasinski, Edward ; Kreuh, Darij ; Lehocká, Denisa ; Melkonyan, Alexander ; Müller, Matthias ; Noble, Paul ; Olshvang, Anton ; Perrone, Diego ; Ondák, Roman ; Osmolovsky, Anatoly ; Paci, Adrian ; Pernice, Manfred ; Philipsz, Susan ; Potrc, Marjetica ; Raila, Arturas ; Knud, Rasmus ; Sala, Anri ; Sangar, Bülent ; Savic-Gecan, Tomo ; Schie 2.0 ; Semper, Ene-Liis ; Stalker ; Starling, Simon ; Stichting De Geuzen ; Skart ; Span, Nika ; Tabatabai, Nasrin ; Tuerlinckx, Joëlle ; Tripp, Sarah ; Tropa, Francisco ; Xhafa, Sislej ; Zivic, Gregor ; Zbanic, Jasmila ; Zvegelj, Janja
Text English-Slovenian
Manifesta 3, European Biennial of Contemporary Art, Ljubljana, 23.6. - 24.9.2000, Cankarjav Dom - Cultural and Congress Centre Ljubljana
kunstcatalogus